Plant elemental composition and portable X‐ray fluorescence (pXRF) spectroscopy: quantification under different analytical parameters. (7th December 2015) - Towett, Erick K.; Shepherd, Keith D.; Lee Drake, B.
Abstract : Emergence of portable X‐ray fluorescence (pXRF) systems presents new opportunities for rapid, low‐cost plant analysis, both as a lab system and in situ system. Numerous studies have extolled the virtues of using pXRF for a wide range of plant applications, however, for many such applications, there is need for further assessment with regards to analytical parameters for plant analysis. While pXRF is a potential powerful research tool for elemental composition analysis, its successful use in plant analysis is made more likely by having an understanding of X‐ray physics, calibration process, and ability to test a variety of homogenous and well‐characterized materials for developing a matrix‐specific calibration. Because potential pXRF users may often underestimate the complexity of proper analysis, this study aims at providing a technical background for plant analysis using pXRF. The focus is on elemental quantification under different analytical parameters and different methods of sample presentation: direct surface contact under vacuum, placement in a sample cup with prolene as a seal, and without the aid of a vacuum. Direct analysis on the surface of a pXRF provided highest sensitivity and accuracy (R 2 > 0.90) for light elements (Mg to P). Sulfur, K, and Ca can be reliably measured without the aid of a vacuum (R 2 > 0.99, 0.97, and 0.93 respectively), although lower detection limits may be compromised. pXRF instruments provide plant data of sufficient accuracy for many applications and will reduce the overall time and budget compared with the use of conventional techniques. Sensitivity and accuracy are dependent on the instrument's settings, make, and model. © 2015 The Authors. X‐Ray Spectrometry published by John Wiley & Sons, Ltd.